Data structures using C++ - Patil, Varsha H. (Oxford higher education., 2012)
Data Structures Using C++ is designed to serve as a textbook for undergraduate engineering students of computer science and information technology as well as postgraduate students of computer applications. The book aims to provide a comprehensive coverage of all the topics related to data structures. The book begins with a discussion on the fundamentals of data structures and algorithms, and moves on to the concepts of linear data structures, stacks, recursion, queues, and searching and sorting. All the elements of data structures, such as linked lists, trees, graphs, hashing, heaps, and indexing, are covered in separate chapters in detail. The chapter on files explains file management and organization using C++ and the chapter on the standard template library provides detailed coverage of entities such as containers and iterators. A chapter on algorithm analysis and design is provided towards the end that discusses the various algorithmic strategies required to solve a problem effectively and efficiently. Written in a simple manner with strong pedagogy including numerous multiple choice and review questions, the book also provides programming problems at the end of every chapter.--Publisher description.